Freshwater mussel shells from three late prehistoric Glenwood locality earthlodge sites in western Iowa analysis of species composition and an assessment of shell modification - Lamb, Elizabeth (My University, 2011)
5203 Freshwater mussel shells were analyzed from three Late Prehistoric Glenwood culture sites (A.D. 1250 ? 1400) in western Iowa. Shells were identified to the species level and all modified shells were segregated for additional analysis and description. Shells of specific shape and texture were selected for some tool types. A newly described tool, referred to as pigment applicators, are described and were successfully replicated through experimental application. The current analysis of shell assemblages are compared to the nearby Wall Ridge site.
Keywords: Historic sites -- Iowa.; Indians of North America -- Iowa -- Antiquities.; Excavations (Archaeology) -- Iowa.